Hi Soo Shin Hepinstall: Growing Up in a Korean Kitchen - Davidson, Alan (Petits Propos Culinaires, 2024)
Hi Soo Shin Hepinstall: Growing Up in a Korean Kitchen: Ten Speed Press, Berkeley, 2001: ISBN 1-58008-281-5: 254 pp., monochrome photos, h/b, 29.95.